Case report: Envafolimab causes local skin necrosis - Liu, Jing Jing; Xu, Xiao Ya; Han, Huan; Wang, Tong; Zhang, Wei; Cui, Jing; Semenov, Maksim (Frontiers in Immunology, 2024)
Envafolimab is a Chinese domestic innovative fusion of a humanized single-domain programmed death-ligand 1 (PD-L1) antibody (dAb) and human immunoglobulin IgG1 crystalline fragment (Fc) developed for subcutaneous injections. It was granted conditional market authorization by the China National Medical Product Administration (NMPA) in December 2021. Envafolimab is used to treat adult patients with previously treated microsatellite instability—high (MSI-H) or deficient mismatch repair (dMMR) advanced solid tumors, including patients with advanced colorectal cancer disease progression who were previously administered fluorouracil, oxaliplatin, and irinotecan, as well as other patients with advanced solid tumors who experienced disease progression after receiving standard treatment and had no other alternative treatment options. However, the lack of post-marketing clinical trial data requires conducting more clinical studies on the safety and efficacy of envafolimab in order to provide scientific basis and a reference for future therapeutic applications. In this paper, we report a case of severe skin necrosis and bleeding in the area of injection after subcutaneous administration of envafolimab in a patient diagnosed with hepatocellular carcinoma. We discuss issues that must be considered before administration of a PD-L1 inhibitor subcutaneously, which could induce immune mechanisms leading to skin necrosis in the area of injection.